The Effect of Genially-Based Learning Media on The Arabic Speaking Skills of Fifth-Grade Students at The Tanjungpinang State Elementary Madrasah - Lia Juniati; Fajar Tresna Utama; Ruddat Ilaina Farkhatun; Dharin Aisyah Syahidah; M. Fadhlurrahman; Kurnia Kurnia; Taskia Rumaisha; Nurhasanah Nurhasanah (Al-Jawhar : Journal of Arabic Language, 2025)
Arabic plays a significant role in developing students' communicative competence in Islamic elementary education. However, traditional instruction has inadvertently transformed speaking skills into the most anxiety-inducing aspect, silencing students' oral production through teacher-centered pedagogy. To address this critical gap, this study aims to examine the effect of Genially-based learning media on the Arabic speaking skills of fifth-grade students at the Tanjungpinang State Elementary Madrasah. This study employs a quantitative, quasi-experimental design with a nonequivalent control group. The study sample consists of two classes: Class 5C (experimental group) and Class 5B (control group), each comprising 33 students. Data collection was conducted through observation, interviews, documentation, and Arabic-speaking skills tests. The data were analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, and the independent samples t-test for hypothesis testing. The study found that the experimental class’s average score increased from 49.94 on the pretest to 74.58 on the posttest, while the control class’s average score increased from 45.34 to 57.88. In percentage terms, the increase in the experimental class reached 49.34%, higher than that of the control class at 27.66%. The results of the independent-samples t-test showed a p-value of 0.000 < 0.05, indicating a significant difference between the two classes. These findings suggest that Genially-based learning media has a positive and significant effect on students’ Arabic speaking skills. This study implies that Genially can serve as an alternative interactive medium to support more engaging, participatory, and student-centred maharah al-kalām learning at the madrasah ibtidaiyah level.